2020
DOI: 10.1016/j.numecd.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Change in abdominal, but not femoral subcutaneous fat CT-radiodensity is associated with improved metabolic profile after bariatric surgery

Abstract: Background and aims: Computed tomography (CT)-derived adipose tissue radiodensity represents a potential noninvasive surrogate marker for lipid deposition and obesity-related metabolic disease risk. We studied the effects of bariatric surgery on CT-derived adipose radiodensities in abdominal and femoral areas and their relationships to circulating metabolites in morbidly obese patients. Methods and results: We examined 23 morbidly obese women who underwent CT imaging before and 6 months after bariatric surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In the present study, low glycine, arginine, and citrulline levels were associated with high VAI. Several studies have associated the non-essential amino acids (glycine and arginine), and citrulline, a metabolite of arginine, with an improved glycemic control [ 45 , 46 , 47 ], lower adiposity, and decreased risk factors for developing metabolic syndrome [ 48 ]. Interestingly, we found enrichment in glycine, serine, and threonine metabolism in our metabolic pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, low glycine, arginine, and citrulline levels were associated with high VAI. Several studies have associated the non-essential amino acids (glycine and arginine), and citrulline, a metabolite of arginine, with an improved glycemic control [ 45 , 46 , 47 ], lower adiposity, and decreased risk factors for developing metabolic syndrome [ 48 ]. Interestingly, we found enrichment in glycine, serine, and threonine metabolism in our metabolic pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of BCAAs catabolism is supported by the consistent postoperative decline of specific subproducts of BCAAs' mitochondrial oxidation, namely short chain acylcarnitine's C3 and C5 [17,18,28,30,43]. Although BCAAs decrease after both restrictive and malabsorptive surgeries [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][35][36][37], parallel arm studies reported a greater effect of RYGB in BCAAs levels [27,31]. Since the differences found in BCAA levels when comparing RYGB and the restrictive procedures seem to be independent of the weight loss, these were hypothesized to be related to impaired AAs absorption induced by the RYGB intestinal rearrangement [27,31].…”
Section: Discussionmentioning
confidence: 94%
“…Numerous studies demonstrated that circulating levels of valine [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], isoleucine [17-24, 26, 27, 29-36], leucine [17-24, 26, 27, 29-33, 35-37], phenylalanine [17,18,20,21,23,24,[26][27][28][29]37], tyrosine [17-21, 23, 24, 27, 29, 30, 37], tryptophan [17,21,24,29,37,38], alanine [17-21, 23, 28, 30, 33, 39], proline [17-19, 21, 28, 39], methionine [18,23,30], aspartate [21], threonine [19,21,32], lysine [19] and ornithine [18,...…”
Section: Metabolomic Profiles Induced By Bariatric Surgerymentioning
confidence: 99%
“… 11 In visceral and subcutaneous adipose tissue, a low radiation attenuation probably is an indicator of high adipose tissue lipid content as it is associated with increased adipocyte size, high adipose tissue mass, and increased serum lipoprotein levels in obese individuals. 12 , 13 While adipose tissue fat content has been poorly studied in cancer, myosteatosis has been associated with decreased overall survival in several cancer types. 14 , 15 , 16 However, the aetiology of myosteatosis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%